Perspective national communication system for cyber management of critical facilities - Tomashevsky, Bogdan; Yevseiev, S. P.; Tkachov, Andrii (Peal Press Ltd., Great Britain, 2020)
In a promising confidential communication system, it is proposed to use special communication systems (networks), special dual-purpose systems, as well as systems of open public Internet systems and mobile communication systems. Secrecy of data transmission, cryptographic strength, authentication and authenticity is ensured by the use of a verbatim container, cryptoalgorithms of protection, hash functions, random switching of transmission channels and blockchain transaction technology.
Keywords: communication system; cyber control; cyber security